Sustainable Management of Tropical Forests Can Reduce Carbon Emissions and Stabilize Timber Production - Sasaki, Nophea; Asner, Gregory P.; Pan, Yude; Knorr, Wolfgang; Durst, Patrick B.; Ma, Hwan O.; Abe, Issei; Lowe, Andrew J.; Koh, Lian P.; Putz, Francis E. (Frontiers in Environmental Science, 2016)
The REDD+ scheme of the United Nations Framework Convention on Climate Change has provided opportunities to manage tropical forests for timber production and carbon emission reductions. To determine the appropriate logging techniques, we analyzed potential timber production and carbon emission reductions under two logging techniques over a 40-year period of selective logging. We found that use of reduced-impact logging (RIL) techniques alone in tropical production forests could reduce carbon emissions equivalent to 29-50% of net emissions from tropical deforestation and land use change, while also supplying 45% of global round-wood demand. Adopting RIL plus (RIL+) other improvements in forest management (adopting forest certification and DNA timber tracking to prevent illegal logging) and wood conversion practices (adopting technology to increase recovery of sawn wood), would result in increasing long-term carbon storage in sawn-wood and reduce logging-induced fire-prone wood wastes by 14-184%. For this to happen, about US$2 billion or $1.86 per Mg CO2 in financial incentives are needed annually for parties to adopt RIL+ and to prevent premature re-entry logging. Our findings suggest that future climate policies explicitly include RIL+ to satisfy the “sustainable management of forests” proviso in the REDD+ scheme, and also count carbon in wood products as eligible credits for trading.